2021
DOI: 10.3390/info12040162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of User Interfaces on Take-Over Performance: A Review of the Empirical Evidence

Abstract: In automated driving, the user interface plays an essential role in guiding transitions between automated and manual driving. This literature review identified 25 studies that explicitly studied the effectiveness of user interfaces in automated driving. Our main selection criterion was how the user interface (UI) affected take-over performance in higher automation levels allowing drivers to take their eyes off the road (SAE3 and SAE4). We categorized user interface (UI) factors from an automated vehicle-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The requirements for such control takeover situations will differ between the respective tasks and contexts, such as when driving automated cars [6,16], managing fleets of automated vehicles in a logistics center [15], or when surveying the quality of an automated manufacturing process [3,18]. The long-term formation of trust in automation and corresponding design patterns for monitoring and interventions are increasingly provided by the HCI research community [8,14], but their applicability across other tasks and contexts is not straightforward.…”
Section: Monitor and Intervenementioning
confidence: 99%
“…The requirements for such control takeover situations will differ between the respective tasks and contexts, such as when driving automated cars [6,16], managing fleets of automated vehicles in a logistics center [15], or when surveying the quality of an automated manufacturing process [3,18]. The long-term formation of trust in automation and corresponding design patterns for monitoring and interventions are increasingly provided by the HCI research community [8,14], but their applicability across other tasks and contexts is not straightforward.…”
Section: Monitor and Intervenementioning
confidence: 99%
“…As described above, the irony of this development is that users are no longer engaged with the automated process, and are thus not able to act quickly when the system needs help. This is a major challenge, e.g., with autonomous cars that may need a human to quickly take over in surprising circumstances [4,16]. Similarly, other automated appliances in our everyday surroundings might prepare their users for manual interventions as well.…”
Section: Engage For Operationmentioning
confidence: 99%
“…Those modality can be used individually or conjointly, and the multimodality of a TOR was shown to indicate urgency and lead to shorter reaction time, compared to a unimodal TOR . Overall, review of the literature showed the potential for advanced UI in conditionally autonomous vehicles (Kim, 2021).…”
Section: Related Work Factors Influencing Takeover Qualitymentioning
confidence: 99%